The effect of compulsory service on life satisfaction and its channels - Matthias Collischon; Andreas Eberl; Kerstin Jahn (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
Compulsory military service is still a prominent feature of young people's careers in many countries. We use the abolition of compulsory military and civil service for males in 2011 in Germany as a natural experiment to identify effects of institutionalized career disruptions on life satisfaction. Drawing on data from the SOEP, we apply a difference-in-differences design (comparing young males and females) to assess the causal effect of this reform on individual life satisfaction. Our results show a significant and robust positive effect of the abolition of compulsory service on young males' life satisfaction. Furthermore, we provide empirical evidence that reductions in career disruptions, forgone earnings, uncertainty regarding the future, and forced labor contribute to this effect. – – In vielen Ländern ist die Wehrpflicht nach wie vor zentraler Bestandteil in den Erwerbskarrieren junger Menschen. Wir nutzen die Abschaffung der Wehrpflicht und des Wehrersatzdienstes für Männer in Deutschland 2011 als natürliches Experiment, um Effekte institutionalisierter Karriereunterbrechungen auf die Lebenszufriedenheit zu untersuchen. In difference-in-difference Analysen der Daten des SOEP vergleichen wir junge Männer und Frauen, um den kausalen Effekt der Reform auf die individuelle Lebenszufriedenheit zu messen. Unsere Ergebnisse zeigen einen signifikanten und robusten positiven Effekt der Abschaffung der Wehrpflicht auf die Lebenszufriedenheit junger Männer. Außerdem weisen die Ergebnisse darauf hin, dass der Effekt durch seltenere Karriereunterbrechungen, Einkommensausfälle, Unsicherheit gegenüber der Zukunft und Zwang zur Arbeit vermittelt wird
Keywords: I31; I38; J18; 330; policy evaluation; military service; happiness; well-being; life satisfaction